Analisis Produksi Usahatani Ubi Kayu (Manihot esculenta) di Desa Pandulangan Kecamatan Telaga Langsat Kabupaten Sungai Selatan - Rizki Hidayati; Luki Anjardiani (Universitas Lambung Mangkurat, 2013)
The objectives of the research were to analyze the cost, return. income. and profit of cassava farming, to find out the production factors influencing the production of cassava, and to find out the problems faced in the cassava farming. The average width of the arable land was 6.97 borong (1 borong = 0.029 ha). The implicit cost of cassava farming was Rp 1,486,421 per farming or Rp 213,352 per borong while the explicit cost was Rp 509,474 per fanning or Rp 73, 127 per borong. The production per farming was 2, 623. 33 kg or 376 56 kg per borong. The income was Rp 4,242,526 per farming or Rp 608,946 per borong. The profit was Rp 2, 756, 106 per farmmg or Rp 395,594 per borong. The result of the simultaneous test indicated that all the production factors (the width of the land, the number of seeds, the fertilizers, the labors, and the herbicides) significantly influenced the production of cassava. However, the partial test showed that only one production factor significantly influencing the cassava production, namely the width of the land. The problems in the cassava farming were the limited capital owned by the farmers resulting in farmers' incapability to enlarge their farming, and the limited knowledge possessed by the farmers about the fertilizer dosage for cassava.